Coherent Enantiomer‐Selective Population Enrichment Using Tailored Microwave Fields. Issue 41 (2nd August 2017) - Pérez, Cristóbal; Steber, Amanda L.; Domingos, Sérgio R.; Krin, Anna; Schmitz, David; Schnell, Melanie
Abstract: We report the experimental demonstration of coherent enantiomer‐selective enrichment of chiral molecules by employing a novel microwave five‐pulse scheme. Our results show that enantiomers can be selectively transferred to a rotational level of choice by applying sequences of resonant microwave pulses in a phase‐ and polarization‐controlled manner. This is achieved by simultaneously exciting all three kinds of electric dipole‐allowed rotational transitions and monitoring the effect on a fourth rotational transition of choice. Using molecular beams, we apply our method to two chiral terpenes and obtain a 6 % enantiomeric enrichment, which is one order of magnitude larger than that recently reported in a buffer‐gas cell experiment. This approach establishes a robust scheme for controlled manipulation of enantiomers using tailored microwave fields and opens up new avenues for chiral purification and enrichment that can be used in a broad scope of analytical or spectroscopic applications. Abstract : Enantiomer‐selective population enrichment can be achieved by simultaneously exciting a chiral sample with three orthogonal microwave pulses. Careful control of the applied fields enables enantiomers to be selectively transferred to a rotational level of choice. Combined with further developments, this result has the potential to open new avenues for chiral analysis.